Maternal Influences and Intervention Strategies on the Development of Food Allergy in Offspring - Jiao, Lefei; Su, Chien-Wen; Cao, Tinglan; Zheng, Shasha; Walker, W. Allan; Shi, Hai Ning (Frontiers in Immunology, 2022)
Food allergies and other immune-mediated diseases have become serious health concerns amongst infants and children in developed and developing countries. The absence of available cures limits disease management to allergen avoidance and symptomatic treatments. Research has suggested that the presence of maternal food allergies may expose the offspring to genetic predisposition, making them more susceptible to allergen sensitization. The following review has focused on epidemiologic studies regarding maternal influences of proneness to develop food allergy in offspring. The search strategy was "food allergy OR maternal effects OR offspring OR prevention". A systematically search from PubMed/MEDLINE, Science Direct and Google Scholar was conducted. Specifically, it discussed the effects of maternal immunity, microbiota, breastfeeding, genotype and allergy exposure on the development of food allergy in offspring. In addition, several commonly utilized prenatal and postpartum strategies to reduce food allergy proneness were presented, including early diagnosis of high-risk infants and various dietary interventions.